PENGEMBANGAN TES HIGHER ORDER THINKING SKILL (HOTS) PADA MATERI SUHU DAN KALOR UNTUK SMA - Agusta, Sela; Sitompul, Stepanus Sahala; Arsyid, Syaiful B (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to developed the Higher Order Thinking Skills (HOTS) test about temperature and heat in senior High School students. The method in this research was developed from Borg and Gall development model which has been simplified into 6 steps, they were collecting data planning, product designing, design revisioning, trial product, product revisioning, and data analysis. The test consists of 10 multiple choise questions with the reason. 85 students were involve in the trial. Based on date analyze, HOTS test developed is proper to used which test characteristic of high validity level, high reability, easy to moderate level of diffcullty and readability index greater or equal to 6. The analysis results of contens validity is 0,75 result of item validity 9 question valid, the reability of this test was 0,616 and readability index of this test was 6,933. So, there werw 9 of 10 developed question that could be used.Â Keywords: Harmonic Vibration, HOTS, Test DevelopmentÂ